Tourism development in rural areas: potentials of appreciative inquiry approach / Roslizawati Che Aziz, Nik Alif Amri Nik Hashim and Zaimatul Awang - Che Aziz, Roslizawati; Nik Hashim, Nik Alif Amri; Awang, Zaimatul (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2018)
This study attempts to examine the way in which rural tourism is developed by using the Appreciative Inquiry (AI) approach as a research tool. AI is an increasingly important area as it was able to offer a positive and strength-based approach to the rural community development. It can be seen as an alternative tourism research tool for community development as far as rural tourism is concerned. The qualitative research approach was applied by conducting focus group discussions with the local communities and youth groups at Sungai Sedim Nature Forest (SSNF) in Kedah, Malaysia. SSNF was chosen as the research setting due to its characteristics and future contributions to a host of residents. From the discussion, natural resources, eco-tourism products, Tree Top Walk and historical assets have been identified as the significant strengths at SSNF. Also, the respondents believe that with the development of these products, it will enhance the image and branding of the SSNF as the best ecotourism destination in Malaysia.